Analisis Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang - Khalyza Qaedaniesa Wibowo; Mawar Mawar (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
The Department of Population and Civil Registration is an agency engaged in the field of public services. Nowadays, many people are aware of the importance of civil registration of Indonesian citizens. Currently there are still many people who feel dissatisfied with the performance provided by employees to the community. This is due to problematic employee performance, such as employee attitudes that are less than friendly, employee performance that does not satisfy the public, and employees not completing their work on time. The aim of this research at the Tangerang City Population and Registration Service is to determine and analyze the performance of employees at the Tangerang City Population and Civil Registration Service. The method used in this research is a descriptive method with a qualitative approach. The results of this study indicate that the performance of employees at the Department of Population and Civil Registration is not optimal. In terms of quality indicators, employee performance still needs to be improved due to the mismatch between job placement and their abilities and skills. On the quantity of work indicator, it can be said that it is quite good because the work plan every year can be carried out properly. In terms of punctuality indicators, it still cannot be said to be optimal, because there are still employees being late in coming to work and employees not being on time in completing work. On the effectiveness indicator, it is quite good, because the facilities and systems in the office are adequate. The independence indicator is quite good, because there has been progress in the employee's initiative in carrying out their duties. In terms of work commitment indicators, the research results show that the responsibilities of employees are good, but there is still a lack of employee discipline when coming to work.